Origin of forest plant species in Pomerania: Czubiński’s hypotheses in comparison to recent research - Popiela, Agnieszka (Biodiversity: Research and Conservation, 2006)
More than 50 years after the time when Czubiński (1950, Bad. Fizjogr. Pol. Zach. 2(4): 339-658) published his hypotheses, the pathways and timing of Holocene migration of 16 forest species into Pomerania (NW Poland) were analysed once more. The analysis was based on recent data on distribution of the species, in the wide setting of the present-day knowledge of phytogeography, palaeobotany and palaeogeography. Czubiński’s hypotheses are still valid to a large extent, but in the present paper a different arrival time of some species is postulated. This mainly results from the progress in palaeobotanical studies and new data. New hypotheses regarding the pathways and time of migration of 16 forest species into Pomerania in the Holocene were developed. The xerothermic forest species entered the territory of Pomerania probably during the Boreal period, i.e. later than Czubiński postulated. Some other species, whose arrival time in Pomerania were supposed to be connected with the beech period, apparently have occurred there at least since the Atlantic period.